The role of leadership style towards innovative behavior among employees : A case study at JHEAINS Kota Kinabalu / Mohd Shah Rizam Surahman - Surahman, Mohd Shah Rizam (2010)
This study was conducted to identify the pattern of innovative behavior among employees in JHEAINS at kota kinabalu, sabah. This study also examined the relationship between leadership styles and innovative behavior of employees in JHEAINS at kota kinabalu, sabah. The samples of respondent are 66 where the questionnaire was distributed in finance and management department and various backgrounds were selected to answer the questionnaire in this research. The results of this study identified that whether government servants were aware and have a positive relationship between leadership style and innovative behavior. The result of this study shows that there is a relationship between the leadership style and innovative behavior in JHEAINS. Most respondents were used leadership style and innovative because they know the important of it to the organization in enhancing the quality of works and performance of the organization. Besides that, there are strongly significant different in service tenure and innovative behavior of the respondent where there has a significant different of them. The level of service tenure has a different with the innovative behavior. It shows that, the longer period of service tenure in JHEAINS, the innovative more behavior they have. Other than that, the results of this study is there has a significant different in innovative behavior and age of the respondent. It also shows that, the mature of age of employees, the more innovative behavior they have.